2016
DOI: 10.1111/jtxs.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging and Progressive Neurological Disease on Swallowing: A Concise Overview

Abstract: Difficulty with swallowing, also known as "dysphagia," is a common consequence of neurologic disease, including a variety of progressive neurologic diseases associated with aging. The effects of various neurogenic degenerative diseases on swallowing may differ substantially, depending on the nature of the condition. However, the process of aging alone also has an impact on swallowing function. In this concise review, a brief overview of normal swallowing and changes in swallowing associated with aging will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
(192 reference statements)
1
7
0
Order By: Relevance
“…These results were consistent with previous researches: the swallowing of the healthy elderly was slower, weaker, and less coordinated than that of young adults; and the transition between the oral and pharyngeal phases of swallowing was also impacted by aging. For instances, increased oro‐pharyngeal transit times and delayed initiation of the pharyngeal phase has been reported in the elderly (Britton, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with previous researches: the swallowing of the healthy elderly was slower, weaker, and less coordinated than that of young adults; and the transition between the oral and pharyngeal phases of swallowing was also impacted by aging. For instances, increased oro‐pharyngeal transit times and delayed initiation of the pharyngeal phase has been reported in the elderly (Britton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature describe age-related changes in swallowing (e.g., (3039)). However, studies in which measures of swallow timing are reported, typically involve small sample sizes, or have looked at specific aspects of swallowing rather than following the bolus from the point of entry into the oral cavity to the point at which the bolus tail passes into the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a decrease in salivary flow or change in saliva composition may have an impact on texture and taste perception (Engelen et al, 2007;Neyraud, 2014). Third, swallowing disorders such as inaccurate initial insertion and foodstuff control, drooling and rapid movements of the tongue as well as delayed swallowing response may also appear with age (Ekberg, & Feinberg, 1991;Britton, 2016). According to Ney, Weiss, Kind, & Robbins (2009), presbyphagia corresponds to a moderate impairment of swallowing function induced by a decrease in mastication and salivation efficiency which in turn compromise the formation of a food bolus easy to swallow.…”
Section: Introductionmentioning
confidence: 99%